Réponses

  • Utilisateur Brainly
2014-03-16T13:48:55+01:00
Résolution:

a)
(2x-5) (x+5) -2x² = 3x -7
2x² + 10x -5x -25 -2x² -3x +7 = 0
2x -18 = 0
2x = 18
x = 9

b)
8x -2 (3x+5) -5 = (7x-2) -6 (x-5)
8x -6x -10 -5 = 7x -2 -6x +30
2x -15 = x + 28
x = 28 + 15
x= 43

c)
1/2 (4x-8) +5x -2 = 4/3 (9x-15) + 7
2x -4 + 5x -2 = 12x -20 +7
7x -6 = 12x -13
-5x = -7
x = 7/5

d)
(3x-5) / 4  - (2x+3)/6 = (5x+5) /2 + (3x-1) /12
3 (3x-5) /12 - 2 (2x+3) / 12  =   6 (5x+5) /12 + (3x+1)/12
9x -15 -4x -6 =  30x +30 + 3x +1
5x -21 = 33x +31
5x -33x = 31 +21
-28x = 52
x= -13/7

e)
2/7 (5x-1) -1/3 (6x-5) = 3x -2
10/7x -2/7 - 2x + 5/3 -3x = -2
10/7 x  -5x  = -2 - 5/3 +2/7
10/7 x -35/7 x = -42/21 -35/21 +6/21
-25/7 x =  -71/21
x = 71/21 * 7/25
x = 71/75

Voilà ! J'espère t'avoir aidé(e) ! :)